Determining factors of the innovative behavior of cooperatives: an analysis of the case of Castilla y León - Peraza Castaneda, Elías Humberto; Gómez García, Jesús María; Aleixandre Mendizábal, Guillermo (REVESCO. Revista de Estudios Cooperativos, 2016)
Cooperatives have a long historical experience in the Spanish economy and have demonstrated their ability to compete against traditional firms in the market. To maintain this capability, while taking advantage of the competitive advantages associated with their idiosyncrasies as social economy enterprises, they should take into consideration that the economy is increasingly globalized and increasingly knowledge-based, especially with regards to technological content. As a consequence, the innovative capacity appears to be a key aspect in order to be able to challenge competitors. This article characterizes the innovative behavior of cooperatives in the region of Castile and Leon and analyses the internal and external factors affecting their innovative performance, based on data from a survey of 581 cooperatives. The results of the empirical analysis, which is performed by multivariate binary logistic regression on various types of innovation, lead us to identify the size of the organizations, the existence of planning, the R & D activities and the human capital as the main determining factors.
Keywords: Multivariate binary logistic regression; Cooperatives; Innovation; Empirical study; Internal and external factors.